An analytical model to investigate the economic and environmental benefits of a supply chain resource-sharing scheme based on collaborative consolidation centres. Issue 12 (2nd December 2018) - Antheaume, Nicolas; Thiel, Daniel; de Corbière, François; Rowe, Frantz; Takeda, Hiro
Abstract: This study evaluates the cost and carbon dioxide-equivalent emissions of different supply chain configurations to determine when suppliers should move to a greener resource-sharing scheme. We build an analytical model based on a case study of a retailer that has developed a resource-sharing initiative introducing collaborative consolidation centres (CCC) between its suppliers and its warehouses (WH). We compare the costs and carbon dioxide-equivalent emissions of using a pair of CCCs with direct delivery to twenty WHs. Our parameters include the distances between suppliers, CCCs, and WHs, in addition to the volumes delivered. This model determines when there should be a switch to the CCC system. We also compare the actual CCC locations with better alternatives, the centres of gravity of the regions. On a real cost basis, economic gains, but not environmental ones, occur, highlighting a need for alternative models for optimal locations, which would include economic and environmental constraints.